2017
DOI: 10.1186/s13561-017-0155-5
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequality of diabetes patients’ health care utilization in Denmark

Abstract: Understanding socioeconomic inequalities in health care is critical for achieving health equity. The aim of this paper is threefold: 1) to quantify inequality in diabetes health care service utilization; 2) to understand determinants of these inequalities in relation to socio-demographic and clinical morbidity factors; and 3) to compare the empirical outcome of using income level and educational level as proxies for Socio Economic Status (SES).Data on the entire Danish population of diabetes patients in 2011 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 39 publications
(46 reference statements)
5
40
2
Order By: Relevance
“…With regard to ethnic differences, we found that men and migrants form the Middle East and Africa were less likely to receive foot examinations or have well-regulated HbA1c, and that some migrant groups scored high on microvascular complications, but the ethnic differences were often not large enough to be verified. The DVDD study does not include data on patient’s socioeconomic position, but recent studies from Denmark have shown clear socioeconomic inequalities in diabetes care utilisation, 24 regulation, 25 complications and survival. 12 …”
Section: Discussionmentioning
confidence: 99%
“…With regard to ethnic differences, we found that men and migrants form the Middle East and Africa were less likely to receive foot examinations or have well-regulated HbA1c, and that some migrant groups scored high on microvascular complications, but the ethnic differences were often not large enough to be verified. The DVDD study does not include data on patient’s socioeconomic position, but recent studies from Denmark have shown clear socioeconomic inequalities in diabetes care utilisation, 24 regulation, 25 complications and survival. 12 …”
Section: Discussionmentioning
confidence: 99%
“…Thus the results do not confirm results from studies of the general population showing that the number of consultations at the GP increases with decreasing socio-economic status [ 15 , 32 ]. The fact that socio-economic differences in mortality and morbidity persist, despite formally equal access to the public health care system, could be due to different use of specialist care as suggested by others [ 17 , 20 ], but this does not seem to be the case for the intervention in our study.…”
Section: Discussionmentioning
confidence: 61%
“…The presented benefit of structured personal care on long-term endpoints, also for patients with low level of education and patients on welfare benefits, cannot be ascribed to single elements of complex interventions. Patients with low level of education and income are frequently reported to be inadequately controlled with hyperglycaemia, hypertension, dyslipidaemia and unhealthy lifestyle [ 14 , 15 ], and some studies also suggest socio-demographic differences in prescription rates [ 16 , 20 ]. Our results are in line with earlier studies, concerning socio-demographic differences of intensive multifactorial interventions, which have been shown not to worsen or introduce social inequity in the control of T2DM [ 13 , 21 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many works support that socioeconomic-related differences exist in diabetes control and care, despite the presence of universal health coverage which may be seen as a facility that ensure the affordability of care. Patients with a lower socioeconomic position (SEP) had a lower rate of control of diabetes [ 1 3 ], lower access to preventive care as suggested by higher complication rates and morbidity [ 1 , 4 8 ], higher general practitioner attendance rates but lower rates of hospital and specialised care attendance [ 1 , 3 , 4 , 9 11 ]. These studies did not account for nor investigate the role of the geographical context despite evidences supporting the influence of the living place on patients’ use of health services, in different healthcare systems.…”
Section: Introductionmentioning
confidence: 99%